The metastability of the proteome of spinal motor neurons underlies their selective vulnerability in ALS. (21st June 2019) - Yerbury, Justin J.; Ooi, Lezanne; Blair, Ian P.; Ciryam, Prajwal; Dobson, Christopher M.; Vendruscolo, Michele
Graphical abstract: Highlights: Spinal motor neuron proteome is supersaturated relative to oculomotor neurons. Proteins corresponding to genes downregulated in ALS are more supersaturated. Proteins encoded by genes upregulated in ALS are less supersaturated. Ion channels and transporters are supersaturated and downregulated. Abstract: Amyotrophic lateral sclerosis (ALS) is a heterogeneous motor neuron disease with familial forms linked to numerous mutations in a range of genes. The resulting variant proteins, including SOD1, TDP-43, and FUS, disturb protein homeostasis in a variety of ways and lead to the formation of intracellular inclusion bodies that are characteristic of different neuropathological subtypes of the disease. These inclusions are made up of scores of proteins that do not appear at first to share obvious characteristics other than coaggregation. Recent evidence, however, suggests that these aggregating proteins can be characterized as being supersaturated in spinal motor neurons, as they exhibit cellular concentrations exceeding their solubilities. Here, we show that the average supersaturation of the entire spinal motor neuron proteome is greater than that of the ALS-resistant oculomotor neurons, suggesting that the vulnerability of spinal motor neurons is linked to the overall metastability of their proteome against aggregation. Consistently, ALS expression data suggest that affected neurons respond to pathology by transcriptional downregulation of supersaturated proteins, including specifically ion channels. These results identify a mechanism by which protein homeostasis imbalance leads to inclusion body formation in ALS, and to a disruption of other processes dependent on proteins that are supersaturated, thereby resulting in the dysfunctional excitability alterations observed in vivo.